Integrin α4β7 Antagonists: Activities, Mechanisms of Action and Therapeutic Prospects - Soler-Ferran, Dulce; J. Briskin, Michael (Current Immunology Reviews (Discontinued), 2012)
The α4β7 integrin is a leukocyte homing receptor with selective tissue tropism for the gastrointestinal tract through its interaction with MAdCAM-1, an adhesion receptor expressed on the endothelium of the gut mucosa. Crohn’s disease (CD) and ulcerative colitis (UC), two inflammatory bowel diseases resulting from intestinal immunedysregulation, are associated with pronounced infiltration of α4β7 positive lymphocytes. This has triggered the development of inhibitors of the α4β7/MAdCAM-1 homing pathway. Vedolizumab is a humanized monoclonal antibody selective for α4β7 that demonstrated efficacy in early clinical studies for the treatment of CD and UC and is currently in phase 3 clinical trials. Targeting of α4β7 is also achieved by less selective therapeutic modalities which also block one of the two other leukocyte integrins that share a subunit with α4β7, namely, α4β1 and αEβ7. Natalizumab is an anti-α4 monoclonal antibody and dual α4β1 and α4β7 antagonist approved for the treatment of multiple sclerosis and CD. Other therapies in development include antibodies targeting the β7 subunit of α4β7 and αEβ7, MAdCAM-1, and dual α4 small molecule antagonists. This review will focus on the mechanism of action, pharmacology, efficacy and safety properties as well as future opportunities that may arise from this unique class of leukocyte anti-adhesion antagonists.
Keywords: vedolizumab